Energy saving technology of acrylamide polymerization in plate reactor based on phase change heat transfer. (5th June 2023) - Xiang, Nan; Li, Chenyang; Yang, Kangbo; Yang, Chengcheng; Guo, Hongshan; Wang, Chuanxing
Highlights: AM with the concentration of above 40% polymerized effectively with plate reactor. Paraffin has better experimental reproducibility and stability. Polyacrylamide colloid thickness is a key factor in controlling heat transfer. Abstract: A new type of plate heat exchanger reactor was designed and studied to transfer the heat of acrylamide polymerization by using phase change heat transfer materials to improve the product performance and alleviate the phenomenon of polymer cross-linking and molecular weight reduction caused by high temperature of acrylamide polymerization. The results showed that the key factor limiting the heat transfer was the thickness of polyacrylamide colloid. Reducing the heat transfer distance could effectively accelerate the heat transfer of polyacrylamide colloid. The paraffin wax has good thermophysical properties and stability. It could maintain a constant temperature in the phase change process during the polymerization. Different monomer concentration acrylamide polymerization process found that the higher the monomer concentration, the better the heat transfer effect, the system temperature change range is reduced to achieve the polymerization process temperature control, reduce energy consumption, energy saving and environmental protection development. Compared with the traditional aqueous solution polymerization process without phase transition heat under the same conditions, the molecular weight of the polyacrylamide polymerization process based on phase transition heat increased by 38.5%. The main mode of heat transfer between the polyacrylamide colloid and the phase change material was determined by numerical calculations as heat conduction.